The organization of the pedagogical work of Federal Institute and the implications to the teaching work - Peratz, Tatiane; Portelinha, Angela Maria Silveira (Universidade Estadual de Campinas, 2019)
This article is the result of the research of a Master’s degree dissertation which has organization of the pedagogical work (OTP) of Instituto Federal do Paraná (IFPR) as its theme. Its object of analysis is the teacher’s work, specifically to what refers to the OTP. The research aims to investigate the implications of the OTP to the teacher’s work and teacher’s education at IFPR – Campus Palmas, Southeast region of Paraná state. The methodology is based on the bibliographic research in which documents and data obtained through questionnaires were answered by twenty four teachers of Campus Palmas. Through the analysis, the vertical expansion of teaching stands out as the main implication for the teacher’s work and education, since this form of organization of the pedagogical work requires action on the distinct levels of education. However, at the same, the vertical expansion is pointed as an implication for the teacher’s work, it is also considered a possibility of learning, since the changes between the levels of education demand a constant professional development and from that the different educational needs emerge. The discussions show contradictions regarding the organization of the pedagogical and the teacher’s work. It also shows contradictions regarding the teachers’ education to work in the Professional Education.